Apyrase Elicits Host Antimicrobial Responses and Resolves Infection in Burns. Issue 6 (November 2016) - Bayliss, Jill M.; Levi, Benjamin; Wu, Jianfeng; Wang, Stewart C.; Su, Grace L.; Xi, Chuanwu
Abstract : The authors previously reported that adenosine triphosphate (ATP) stimulates biofilm formation and removal of the ATP could reduce biofilm formation. The main objective of this study was to evaluate the effects of the ATP-hydrolyzing enzyme, apyrase, on control of Acinetabacter baumannii infection in the burn wound as well as to assess host skin antimicrobial responses. The authors found that apyrase stimulated nitric oxide formation at the wound site and reduced CD55 expression, thereby inducing the assembly of membrane attack complexes. Apyrase treatment nearly eradicated multidrug-resistant A. baumannii from burn wounds in the absence of antibiotics. Apyrase may be an effective therapy against antibiotic-resistant bacterial infections in burns.